Effect of air-gap fans on cooling of windings in a large-capacity, high-speed induction motor. (5th May 2016) - Kim, Chiwon; Lee, Kwan-Soo; Yook, Se-Jin
Highlights: A 3D numerical analysis was performed to analyze the effects of air-gap fan. A novel mapping method considering time and rotation period was introduced. Total winding cooling performance was improved by 55% with both side air-gap fans. For single fan performance, a rear-side fan was more effective than a front-side fan. Abstract: A 3D computational electromagnetic-thermal coupled analysis was performed to analyze the effects of auxiliary cooling fans, called air-gap fans, on winding cooling in a large-capacity, high-speed induction motor. A novel non-uniform iron loss distribution mapping method considering time and rotation period was introduced to provide more accurate thermal modeling. Winding cooling performance in the motor was calculated and evaluated by considering the variation in thermal-fluid characteristics and thermal flow resulting from the air-gap fans. Results showed that flow rate distributed to the air gap was increased as the stagnant flow disappeared near the air gap because of the air-gap fans. The convective heat transfer coefficient on the winding surface was enhanced by the increased velocity of the internal flow. The heat transfer coefficients at the winding surface and air gap were increased up to 31% and 90%, respectively, due to the increased flow rate. Total winding cooling performance was improved, on average, by 55% with front- and rear-side air-gap fans. For single fan performance, a rear-side air-gap fan was more effective than a front-side air-gap fan.